COMPARING THE PRODUCTIVE PERFORMANCE OF BROILER HYBRIDS RESULTING FROM THREE AND FOUR WAY CROSSES - Nahil M. Ali (Mesopotamia Journal of Agriculture)
This study was conducted at the poultry farm of the College of Agriculture and Forestry – Hammam – Alalil. The objectives of this study were to compare the productive performance of the three – way cross broiler chicks (ABD) with that of the four – way cross broiler chicks ( ABCD). Data revealed that there were significant difference (p  0.05 ) between 8 week body weight of three – way cross chicks compared with four –way cross chicks. No significant differences , were observed in feed conversion ratio and percent mortality between the two crosses .